Assessing the impacts of a peer-to-peer training programme for women in Peru. Issue 6 (18th August 2018) - Zegarra, Eduardo; Higuchi, Angie; Vargas, Ricardo
ABSTRACT: This article reports on research that aimed to assess the economic and social impacts of a peer-to-peer training programme targeted to women in Peru, looking at overall and differentiated impacts according to design features, on a sample of 300 women in participant and non-participant communities. The study found significant positive impacts on women's time devoted to work outside the house and in their saving propensity, although no significant change on time allocated to domestic activities. It also detected some effects on an index of family cohesion and on home improvements. Finally, there was evidence that some design features influence the magnitude and significance of these impacts.